The Leadership Challenge : How to Make Extraordinary Things Happen in Organizations, Fifth Edition - Kouzes, James; Posner, Barry ([Place of publication not identified] : John Wiley & Sons (US), 2012)
Focusing on the toughest organizational challenges leaders face today, this indispensable landmark resource addresses changes in how people work and what people want from their work. --
Includes bibliographical references.
Online resource; title from title screen (Books24x7.com).
Keywords: Leadership; Executive ability; Management; Executive ability